PENGARUH SENAM ZUMBA TERHADAP PERUBAHAN KADAR GLUKOSA DARAH - Rike Chessa Sartika; Agung Riyadi; Widia Lestari (JURNAL PENELITIAN TERAPAN KESEHATAN, 2020)
Abstract: Hyperglycemia is one of the causes of chronic DM disease that is most experienced by the world's population and ranks fourth cause of death. The purpose of this study was to determine the effect of zumba gymnastics on changes in blood glucose levels in middle adulthood in the Bengkulu City East Rim Health Center Work Area in 2018. The study design was quasi experimental with pre-test and post-test with control group design. A total sample of 34 people consisted of 17 control groups and 17 intervention groups. The sampling technique is consequtive sampling. Measuring blood glucose levels using Glucose test GlucoDr brand, analysis using t-test at α ≤ 0.05%. The results showed that there was influence of zumba gymnastics on changes in blood glucose levels. Zumba exercises can be useful for controlling and reducing blood glucose levels.Keywords: Zumba, Glucose, Adult.